The Effect of Concentration Variation of Liquid Organic Fertilizer Application on the Growth of Mustard Plants - Nadya Amalia Putri Hapsari; Suparno Suparno (Jurnal Penelitian Pendidikan IPA, 2023)
This study aimed to determine the effect of giving Infarm POC concentration variations on the growth of green mustard (Brassica juncea L). The research employed a completely randomized design (CRD) or randomized block design with 6 treatments and 5 replications, resulting in a total of 30 experimental units. The data collection method and mechanism used involved implementing a completely randomized design (CRD) with 6 types of treatment and 5 replications, leading to the cultivation of 30 mustard plants with POC concentrations ranging from 2% to 10%. The findings revealed that the application of POC fertilizer to mustard plants resulted in increased plant height, leaf count, and resistance to leaf pests. Notably, the POC concentration of 6% exhibited the most significant improvements in plant height and leaf count. However, to gain a more comprehensive understanding of the effectiveness of this POC, further research is necessary. It is recommended to extend the duration of the study until harvest to assess the weight and quality of the mustard greens, thereby providing more conclusive insights